Judge’s Misinterpretation in Assesing the Legalityof Termination of Emploment Due to Company Loses without Audit Evidence - Nurhayati Nurhayati; Muhammad Abdul Zalil; Adlan Khoerul Abdi (PT. Riset Press International, 2026)
This study examines judicial interpretation in assessing the legality of termination of employment due to company losses, focusing on the absence of audited financial evidence. The issue arises from a discrepancy between normative legal standards and judicial practice, particularly in Decision Number 1240 K/Pdt.Sus-PHI/2024. This research aims to analyze the legal requirements governing termination based on company losses and to evaluate whether the court’s reasoning aligns with statutory provisions. The study employs a normative juridical method with a case approach, analyzing legislation and judicial considerations. The findings indicate that the court accepted the company’s loss argument without rigorous verification of objective evidence, especially audited financial statements. Moreover, the decision conflates the fulfillment of workers’ rights with the legality of termination, which normatively constitutes two distinct legal aspects. Procedural requirements, including the obligation to treat termination as a last resort, were also not thoroughly examined. These inconsistencies demonstrate a deviation from established legal standards in both substantive and evidentiary aspects. The study concludes that the decision reflects a gap between legal norms and judicial application, which potentially weakens worker protection. Strengthening judicial consistency in applying evidentiary standards is essential to ensure legal certainty and fairness in industrial relations disputes. This study contributes to the development of labor law discourse by emphasizing the importance of cumulative legal standards in assessing the legality of termination due to company losses, particularly regarding evidentiary standards, audited financial statements, and the distinction between the legality of termination and the fulfillment of workers’ rights.